Association of peripheral NK cell counts with Helios+IFN-γ- T regs in patients with good long-term renal allograft function - Trojan, Karina; Zhu, Li; Aly, Mostafa Gaafa; Morath, Christian; Opelz, Gerhard; Daniel, Volker (Clinical & experimental immunology, 2017)
Little is known about a possible interaction of natural killer (NK) cells with regulatory T cells (Treg) in long-term stable kidney transplant recipients. Absolute counts of lymphocyte and Treg subsets were studied in whole blood samples of 136 long-term stable renal transplant recipients and 52 healthy controls using eight-colour fluorescence flow cytometry. Patients were 1946 ± 2201 days (153-10 268 days) post-transplant and showed a serum creatinine of 1·7 ± 0·7 mg/dl. Renal transplant recipients investigated > 1·5 years post-transplant showed higher total NK cell counts than recipients studied < 1·5 years after transplantation (P = 0·006). High NK cells were associated with high glomerular filtration rate (P = 0·002) and low serum creatinine (P = 0·005). Interestingly, high NK cells were associated with high CD4+CD25+CD127-forkhead box protein 3 (FoxP3+) Treg that co-express the phenotype Helios+interferon (IFN)-γ- and appear to have stable FoxP3 expression and originate from the thymus. Furthermore, high total NK cells were associated with Treg that co-express the phenotypes interleukin (IL)−10-transforming growth factor (TGF)-β+ (P = 0·013), CD183+CD62L- (P = 0·003), CD183+CD62+(P = 0·001), CD183-CD62L+ (P = 0·002), CD252-CD152+ (P < 0·001), CD28+human leucocyte antigen D-related (HLA-DR-) (P = 0·002), CD28+HLA-DR+ (P < 0·001), CD95+CD178- (P < 0·001) and CD279-CD152+ (P < 0·001), suggesting that these activated Treg home in peripheral tissues and suppress effector cells via TGF-β and cytotoxic T lymphocyte-associated protein 4 (CTLA-4). The higher numbers of NK and Treg cell counts in patients with long-term good allograft function and the statistical association of these two lymphocyte subsets with each other suggest a direct or indirect (via DC) interaction of these cell subpopulations that contributes to good long-term allograft acceptance. Moreover, we speculate that regulatory NK cells are formed late post-transplant that are able to inhibit graft-reactive effector cells.